Evaluasi Efektivitas Program Literasi dan Numerasi di SDNegeri 1 Labuan Tereng - Febriana, Vina; Jaelani, Abdul Kadir (Mataram University, 2026)
This study aimed to evaluate the effectiveness of the implementation of the literacy and numeracy program at SD Negeri 1 Labuan Tereng using the CIPP evaluation model (Context, Input, Process, Product). The study was motivated by the school’s need to improve students’ reading and numeracy skills, which were still at a basic level. A descriptive evaluative approach was employed, with data collected through observation, interviews, and documentation. The results of the context aspect indicate that the program was implemented in accordance with the school’s needs and aligned with the Merdeka Curriculum policy and the School Literacy Movement. In the input aspect, the school had supporting facilities such as reading corners, reading materials, numeracy teaching aids, and teacher support; however, improvements are still needed in numeracy training and the variety of reading materials. In the process aspect, the program was implemented fairly well through 15-minute reading activities, the use of reading corners, and contextual numeracy learning, although the consistency of implementation varied among classes and was still constrained by students’ motivation. In the product aspect, the program showed positive outcomes in improving students’ literacy and numeracy skills, although the improvements were not evenly distributed, mainly due to differences in learning support at home. Overall, the literacy and numeracy program at SD Negeri 1 Labuan Tereng was considered moderately effective. Nevertheless, improvements in the quality of facilities, teacher training, and parental involvement are important factors to optimize the program’s outcomes in the future.